ANALISA TINGKAT KEPUASAN PELANGGAN DENGAN METODE FUZZY SERVQUAL - Erma Delima Sikumbang (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Increasing number of businesses in the service of making advertising boards have a negative impact on turnover Advertising revenues, issues regarding the service, also often complained by consumers. In order to attempt to improve the quality of customer service we perform a study of the level of customer satisfaction. This study uses Fuzzy Servqual. The data analysis method used is the Gap Analysis Servqual four dimension is the difference between the expected service to the service received by the customer. And Fuzzy Analysis to determine the gap with defuzzification process. After processing the data in each dimension, it can be seen that the whole dimension has a positive value unless the dimension Empathy is the gap value of -0.426. If viewed from all four dimensions, quality service has met the customer satisfaction level expected by customers.Keyword- Service Quality, Fuzzy Servqual, Perceptions and Expectations